Ingestion of whey protein and β-conglycinin exerts opposite effects on intestinal FGF15 and serotonin secretion in mice - Nonogaki, Katsunori; Kaji, Takao (Frontiers in Endocrinology, 2023)
Farnesoid X receptor (FXR) and Takeda G protein-coupled Receptor 5 (TGR5), the intestinal bile acid (BA) receptors, regulate the gut-derived hormones including fibroblast growth factor 15/19 (FGF15/19) and serotonin (5-hydrooxytryptamine, 5-HT). Here we show that ingestion of whey protein isolate, a milk protein, significantly decreased expression of heteromeric organic solute transporter Ostalpha and Ostbeta, which is the basolateral BA transporter in the enterocyte, and increased the expression of FXR and FGF15 in C57BL6J mouse ileum and plasma FGF15 levels. In addition, the ingestion of whey protein isolate significantly suppressed expression of hepatic cholesterol-7α hydroxylase (CYP7A1), which induces the primary BA synthesis, bile salt export pump (BSEP) and sodium-taurocholate cotransporting polypeptide (NTCP), which are the key transporters for the BA excretion and uptake in the liver, and genes involved in gluconeogenesis, and decreased the primary BAs including cholic acid, taurocholic acid, glycocholic acid, and taurochenodeoxycholic acid in the liver compared with controls. Moreover, ingestion of whey protein isolate significantly decreased the expression of TGR5, glucagon-like peptide 1 (GLP-1), and tryptophan hydroxylase1 (Tph1) in the small intestine, leading to decreases in plasma 5-HT and insulin levels. On the other hand, ingestion of the soy protein beta-conglycinin significantly increased the expression of Ostalpha and Ostbeta and decreased the expression of FGF15 in the ileum and plasma FGF15 levels, leading to the increases in expression of hepatic CYP7A1, BSEP, NTCP, and genes involved in gluconeogenesis, and the primary BAs in the liver. Moreover, ingestion of beta-conglycinin significantly increased the expression of intestinal TGR5, GLP-1, and Tph1, leading to increases in plasma 5-HT and insulin levels. These findings suggest that whey protein and beta-conglycinin have opposite effects on intestinal FGF15 and 5-HT secretion in mice.